Strategi Pengembangan Wisata Bahari Pulau Karampuang Kabupaten Mamuju, Provinsi Sulawesi Barat - Satriadi Lomban; Kamran Aksa; Ilham Yahya (Journal of Urban Planning Studies, 2021)
Abstract. This study aims to identify the significant factors in the development of marine tourism in Karampuang Island and its development strategy. This research uses quantitative and qualitative  approaches. To determine the factors that have a significant effect on the development of the Karampuang Island Marine Tourism Object, the chi square analysis tool is used, while the analysis SWOT is used to formulate a strategy for the development of the Karampuang Island Marine Tourism Object. Based on the results of the Chi-Square test, it is found that the variables of tourism support facilities, safety and comfort, and accessibility do not have a significant effect on the development of the Karampuang Island Marine Tourism Object, while the variables of tourist attraction and information and promotion are the most significant factors. The strategy for developing the Karampuang Island Marine Tourism Object is improving tourism facilities and infrastructure, increasing the role of the government and private sector, increasing tourism information and promotion, improving the quality of human resources (HR), utilizing the potential of tourist attractions, and environmental preservation.   Abstrak. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor apa saja yang signifikan dalam pengenbangan wisata bahari pulau Karampuang serta strategi pengembangannya. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif (deskriptif). Untuk mengetahui faktor yang berpengaruh signifikan terhadap pengembangan Obyek Wisata Bahari Pulau Karampuang digunakan alat analisis chi kuadrat (chi square), sedangkan analisis (SWOT) digunakan untuk merumuskan strategi pengembangan Obyek Wisata Bahari Pulau Karampuang. Berdasarkan hasil uji Chi-Square diperoleh bahwa variabel sarana penunjang wisata, keamanan dan kenyamanan, serta aksesibilitas tidak berpengaruh signifikan terhadap pengembangan Obyek Wisata Bahari Pulau Karampuang, sedangkan variabel daya tarik wisata dan informasi dan promosi merupakan faktor yang paling berpengaruh signifikan. Adapun startegi pengembangan Obyek Wisata Bahari Pulau Karampuang adalah meningkatkan sarana dan prasarana parwisata, peningkatan peran pemerintah dan swasta, peningkatan informasi dan promosi wisata, peningkatan kualitas sumber daya manusia (SDM), memanfaatkan potensi dayatarik objek wisata, serta pelestarian lingkungan.